PENGARUH PENDEKATAN KONTEKSTUAL BERBASIS MULTIPLE INTELLIGENCES (KECERDASAN LOGIS-MATEMATIS DAN VISUAL-SPASIAL ) TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA SEKOLAH DASAR - Supriati, Intan Pratiwi; Irawati, Riana; Kurnia, Dadang (Jurnal Pena Ilmiah, 2019)
This research is based on the idea of mathematical representation's ability that needed by students to find ways of thinking in their communicating mathematical ideas. The representation's ability can be one of the other supporting competencies. This research used multiple intelligences-based of contextual approaches with highlighted intellegences, that are logical-mathematical and visual-spatial intelligence in the context of cube volume and cuboid volume. The purpose of this reasearch was to find the effect of mathematical representation's ability approached and the relationship between mathematical representation's ability and logical-mathematical and visual-spatial intelligence. The method that used of this research was non equivalent control group design. The sample was the fifth grade students of Citarik Elementary School as the experimental class and Tenjolaya III Elementary School as the control class. The data in this research are quantitative and qualitative data that originating from research instruments. The results of this research on multiple intelligences-based contextual approaches (logical-mathematical and visual-spatial intelligence) have a positive effect on representation ability significantly compared to the control class. This reasearch showed a strong correlation between logical-mathematical and visual-spatial intelligence simultaneously with the ability of mathematical representation. However, if the intelligence is not simultaneous, there is a positive effect between mathematical representation and visual-spatial intelligence.